Effect of of Food Quality, Perceived Value, Price Fairness, and Customer Satisfaction on Repurchase Intention and Word of Mouth - Mukaromah, Hajar (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study investigates the influence of Food Quality, Perceived Value, Price Fairness, and Customer Satisfaction on Repurchase Intention and Word of Mouth in the context of offline organic rice sales.A sample of 125 respondents was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between variables. The findings reveal that Food Quality positively affects Price Fairness and Customer Satisfaction, while Price Fairness also positively impacts Perceived Value. In turn, Perceived Value enhances Customer Satisfaction, and Customer Satisfaction leads to higher Repurchase Intention and Word of Mouth. Of the eight proposed hypotheses, six were accepted (H1, H3, H4, H6, H7, H8), while two (H2 and H5) were rejected. Future researchers should consider these variables carefully to avoid inconsistent results. In this study, the Revisit Intention variable was adjusted to Repurchase Intention for better alignment with the research context.